Halal Studies In Universities: A Way Forward To Manage Halal Business - Hasan, Ahmad; Ahmad Fazullah, Ahmad Zainal Abidin; Abd Jalil, Borham (2011)
The understanding of Halal among muslims has been limited to a mere permissible food theory for many decades. Today, this simple theory couldn’t longer work with the large expansion of the halal realm as it enters new attractive global business. Halal brand products have grown in many areas of non-food business such as banking, pharmaceutical, trading, tourism, logistics and many more, which require strong halal knowledge management in tandem. Halal studies inuniversities seem as the right platform to prepare qualified people in the halal industries worldwide. This paper highlights visionary role played by educational institutions in countries like Malaysia, Thailand and Indonesia, and other countries in building platform for comprehensive halal knowledge. Halal Product Research Institute of University Putra Malaysia and Halal Industry Research Centre of International Islamic University Malaysia for instance has embarked into strengthening halal knowledge through their courses, research, collaboration, product development and commercialization. In due discussion, maiden curriculum design for halal lead by the Universiti Malaysia Pahang will also be revealed. In another development, Malaysia has been leading the world for halal affairs since 2006 when it established the first world conference on halal called World Halal Forum (WHF) and latter in 2010 extended it to World Halal Research (WHR). European countries and United State of America has also given significant attention to halal studies or market especially for business purposes. In conclusion, with the halal annual transaction reaching nearly USD3 trillion now, halal definitely will soar into big business in the future and halal studies may undoubtedly be one of the most sought after course and universities’ next course of action.